Odpowiedzi

2010-03-06T18:08:55+01:00
A) x+y= -6
x= -7
y= 1

(-7) +1= -6

Najlepsza Odpowiedź!
2010-03-06T18:16:01+01:00
A)
x + y = -6
x = -7

-7+y=-6
y=-6+7
y=1

b)
x+ 5y = 0
y=1

x+5*1=0
x=-5

c)
x+y = -9
x=2y

2y+y=-9
3y=-9
y=-3

x=2*(-3)
x=-6

d)
x+2y = -5
y-x=8

x=-5-2y
y-(-5-2y)=8
3y=3
y=1

x=-5-2*1
x=-5-2
x=-7

e)
x+2y=-1
2x+3y=-5

x=-1-2y
2(-1-2y)+3y=-5
-2-4y+3y=-5
-y=-3
y=3

x=-1-2*3
x=-1-6
x=-7

f)
x=-2y
y-3x=21

y-3(-2y)=21
y+6y=21
7y=21
y=3

x=-2*3
x=-6

g)
x+2y=0
3x-4y=-20

x=-2y
3(-2y)-4y=-20
-6y-4y=-20
-10y=-20
y=2

x=-2*2
x=-4

h)
2x+5y= -7
x-2y=10

2x+5y= -7
x=10+2y

2(10+2y)+5y=-7
20+4y+5y=-7
9y=-27
y=-3

x=10+2*(-3)
x=10-6
x=4